KERAGAMAN KOMPONEN KIMIA GAHARU PADA KELAS SUPER DAN KEMEDANGAN - Gunawan Pasaribu; Totok K.Waluyo; Gustan Pari (BRIN Publishing, 2015)
This paper presents to the resin content and the chemical composition in agarwood with several quality using gas chromatography mass spectrometry. The agarwood qualities as tested were those super and kemedangan classes originated from Bangka, Papua and Assosiation of Indosnesia's Agarwood Exportry Enterprise (Asgarin). Results revealed the resin yield of super quality agarwood was higher than that of kemedangan-quality counterpart. Agarwood with high resin content was regarded a high (super) quality, and its chemical composition was predominantly chromone and gamma gurjunene. On the contrary, agarwood with low quality (kemedangan) chemicallyy comprised 2.5 furandione, 3-dodecenyl and agarospirol. Further super-quality agarwood chemically contained more sesquiterpene than kemedangan-quality. Sesquiterpene and chromone compound were indicatively responsible the fragrant arome revealed by agarwood. The quality of agarwood in the same quality class but originated from different regions revealed the resin content as well as chemical composition which was different fromeach other.